Improving results of renal transplantation in small children - Ulrich, Frank; Mehrabi, Arianeb; Drehmer, Ingo; Tönshoff, Burkhard; Staehler, Gerd; Wiesel, Manfred (Transplantation proceedings, 1999)
Renal transplantation has become the standard therapy for children with end-stage kidney disease. Development and lifestyle are much better when compared with dialysis. Graft survival rates have been improved due to advances in immunosuppressive therapy, but still have not reached the results of transplantation in adults. Possible reasons are noncompliance in the pediatric renal transplant population,10 congenital anomalies of the urinary tract,11 particular demands in the technique of transplantation, and a faster metabolism of cyclosporine in small children. In a retrospective study we show our results and experiences with this pediatric population. The evaluation, operative therapy and follow-up of our patients was part of a close cooperation between urologists and pediatric nephrologists.
Gesehen am 27.01.2021